The tablet or Moderation, of Charles the First; martyr : With an alarum to the subjects of England - Arnway, John, 1601-1653 (Hague : [s.n.], printed. 1650., 1650)
204 p
By John Arnway.;Reproduction of the original in the British Library.;Wing (2nd ed., 1994) A3738.;Available electronically as part of Early English books online.